CHROMITE-PLATINUM MINERALIZATION OF CLINOPYROXENITE-DUNITE MASSIF ZHELTAYA SOPKA, NORTH URAL - I.A. Kuzmin; R.S. Palamarchuk; V.M. Kalugin; A.V. Kozlov; D.A. Varlamov (Минералогия)
The paper presents the new data on platinum group minerals (PGM) and chromite from the Zheltaya Sopka massif, North Urals. Few chromite bodies along with specific composition of chromite indicate weak ore-forming processes developed in this massif. Minakawaite (RhSb) and chengdeite (Ir3 Fe) are found for the first time in the Uralian Platinum Belt. The PGM assemblage of the Zheltaya Sopka massif is compared with that of the Iov, Yuda, and Sosnovsky dunite massifs of the northern part of the Uralian Platinum Belt. As a result, similar PGM assemblages with dominant minerals of late assemblages are established in dunites of the Zheltaya Sopka massif. Chromites of the massif show no evident chromite-magnetite trend typical of clinopyroxenite-dunite massifs of the Urals and are relatively enriched in Cr2 O3 and Al2 O3 in comparison with chromite of other UPB massifs.